(untitled) - Vorstand der Deutschen Vereinigung für Politikwissenschaft (PVS Politische Vierteljahresschrift, 2013)
Current Rese arch Findings and Controversial Discussions from all areas and sub-areas of Political Science: Politische Vierteljahresschrift (PVS) has been published since 1960 by the executive and advisory board of the German Association for Political Science (DVPW). The journal provides space for recent research findings from all sub-areas of political science. It therefore contains papers on political theory and the history of ideas; on comparative governance and politics; the domains of policy analysis, international relations and foreign policy; on political sociology; and papers in the areas of empirical social research and methodology. The PVS contains four categories of articles : The critical papers form the core category of the journal. In this section, are published theory-based and methodically reflected articles from all sub-areas of political science. Within the forum section, contemporary scientific controversies are debated. The commentaries contain scientifically well-grounded statements with reference to current issues of political developments or to the field of political science. The review essays provide a broad overview of the international state of the art of political science, as well as current developments and relevant published literature regarding a particular research-field. The PVS-Literatur publishes reviews of single publications from all sub-fields of the discipline of political sciences, as well as accumulative reviews presenting more than one new publication within an area of political sciences. Every paper published in the PVS (within the categories critical papers and forum) is run through a double-blind expertise process prior to publication. Generally, two external referees examine the anonymous manuscripts. The referee reports are also made anonymous before being handed back to the authors. Additionally, the authors can be provided with references from the editorial board. The editors rely on the collaboration of the colleagues in the scientific discipline as their referees and reviewers. Anyone interested in being a referee or reviewer is welcomed to complete and submit the PVS-reviewer-form or referee-form to the editor. Next to your name and address please indicate your field of investigative interest as well. This information will be added to the editorial database. Website: www.pvs.nomos.de